MOCVD Growth and Fabrication of High Power MUTC Photodiodes Using InGaAs-InP System. (23rd November 2015) - Singh, Nandan; Ho, Charles Kin Fai; Tina, Guo Xin; Chandra Mohan, Manoj Kumar; Lee, Kenneth Eng Kian; Wang, Hong; Lam, Huy Quoc
Abstract : We report charge-compensated modified uni-traveling-carrier photodiodes (MUTC-PDs) with high photocurrent and fast response, grown using liquid group-V precursor, in an AIXTRON MOCVD system. The liquid group-V precursors involve less toxicity with better decomposition characteristics. Device fabrication is completed with standard processing techniques with BCB passivation. DC and RF measurements are carried out using a single mode fiber at 1.55  μ m. For a 24- μ m-diameter device (with diode ideality factor of 1.34), the dark current is 32.5 nA and the 3-dB bandwidth is ≫20 GHz at a reverse bias of 5 V, which are comparable to the theoretical values. High photocurrent of over 150.0 mA from larger diameter (>60  μ m) devices is obtained. The maximum DC responsivity at 1.55  μ m wavelength is 0.51 A/W, without antireflection coating. These photodiodes play a key role in the progress of the future THz communication systems.